Innovation of the utilization of sale banana (pisang sale) made from awak banana (Musa paradisiaca cv. Awak) and kepok banana (Musa acuminata balbisiana Colla) into skin moisturizer (Inovasi pemanfaatan pisang sale yang terbuat dari pisang awak (Musa paradisiaca cv. Awak) dan pisang kepok (Musa acuminata balbisiana Colla) menjadi pelembab kulit) - Lestari, Wahyu; Meutia, Rita; Saputra, Mulia (Universitas Syiah Kuala, 2022)
Banana is one of the common fruits in Indonesia that can be processed into other products, such as Sale Banana which is one of the typical souvenirs from Aceh. The purpose of this community service activity (PkM) is to increase the income of business owners and Sale Banana traders. The community service location is dedicated to small and medium enterprises in Alue Naga Village, Banda Aceh. Through this PkM activities, Sale Banana is used to create a new product that is a moisturizing product for the skin. Two types of bananas are used in this PkM, namely Awak banana and Kepok banana. The extracts of the two bananas are used as the main ingredient of the moisturizer. The antioxidant activity of the two banana extracts was tested using the DPPH method. Based on the results of community service, skin moisturizers have an IC50 antioxidant activity of 10.52 (Kepok banana) and 14.00 (Awak banana). It could be concluded that both Sale Kepok Banana extract and Awak Banana extract have a strong antioxidant activity and could be used as a good moisturizer.